Relationship of lean mass and obesity in Indian urban children and adolescents - M K Garg (Indian Journal of Endocrinology and Metabolism, 2016)
Background: The association of obesity and lean mass (LM) has not been examined well in children and adolescents, and it remains controversial. Objective: The objective of this study was to evaluate the relationship of body mass index (BMI) categories and regional obesity with total and regional LM in children and adolescents. Methods: A total of 1408 children and adolescents (boys 58.9%; girls 41.1%) divided according to BMI (normal weight 79.5%, overweight 16.0%, and obese 4.5%) were included in this cross-sectional study. Total and regional LM and fat mass were measured by DXA. Leg and arm fat-to-total fat ratio (LATR) indicative of subcutaneous fat and trunk fat-to-total fat ratio (TTR), an indicator of visceral fat, were calculated. Results: Mean age of the study population was 13.2 ± 2.7 years (boys - 13.0 ± 2.7; girls - 13.4 ± 2.8 years). Total LM (TLM) and its regional distribution were higher in overweight and obese groups when compared with those with normal BMI in both genders. TLM was comparable between overweight and obese in both genders. TLM per unit of fat progressively decreased from normal to obese categories. The difference in LM per unit fat between BMI categories persisted after adjustment for age, height, and sexual maturity score. TLM increased across the quartiles of TTR, but decreased with an increment in subcutaneous fat (quartiles of LATR). Conclusions: Obese children and adolescents apparently have higher LM than normal BMI children, but have lower LM per unit of fat. Subcutaneous fat had a negative impact and visceral fat had a positive impact on TLM.